2018
DOI: 10.2174/1570162x16666180717115614
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Demographic, Epidemiological, Immunological, and Clinical Characteristics of Patients with HIV Mono-infection Versus Patients Co-infected with HCV or/and HBV: A Serbian Cohort Study

Abstract: HIV/HCV co-infection was found to be more prevalent than HIV/HBV co-infection in a Serbian cohort. Co-infection with HCV was related to more profound immunodeficiency prior to therapy initiation, reflecting a possible unfavorable impact of HCV on the natural history of HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
1
1
0
Order By: Relevance
“…The higher the feature score is, the more contribution a variable makes to the detective of coinfected with HBV patients in HIV cases. PLA was the most accurate variable in our study, closely followed by CR, AST, HB, ALT, TBIL, leucocyte, age, marital status, and treatment condition, which is similar to previous studies [33][34][35]. PLA had the highest detective value in the heterosexual group, followed by ALT, AST, TBIL, leucocyte, and symptom severity.…”
Section: Discussionsupporting
confidence: 90%
“…The higher the feature score is, the more contribution a variable makes to the detective of coinfected with HBV patients in HIV cases. PLA was the most accurate variable in our study, closely followed by CR, AST, HB, ALT, TBIL, leucocyte, age, marital status, and treatment condition, which is similar to previous studies [33][34][35]. PLA had the highest detective value in the heterosexual group, followed by ALT, AST, TBIL, leucocyte, and symptom severity.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we report a cohort of 389 patients with laboratory‐confirmed SARS‐CoV‐2 infection. Most patients presented with fever, cough and fatigue, which share similar clinical features with previous beta‐coronavirus infections, such as SARS and Middle East respiratory syndrome (MERS) [9,10]. Highly pathogenic human coronaviruses (hCoV) infections frequently lead to lower respiratory tract disease, and disease severity was influenced by initial viral titers in airways, age and co‐morbid conditions [6,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…[HIV], determinando a coinfecção HIV-HCV, o que pode mudar o curso natural da história da infecção pelo HCV [3][4][5][6] .…”
Section: Introductionunclassified